Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the given system of equations using the addition method, follow these steps:
1. Write down the given system of equations:
[tex]\[ \begin{cases} 7x + 3y = 10 \quad \text{(Equation 1)} \\ 4x + 4y = 8 \quad \text{(Equation 2)} \end{cases} \][/tex]
2. Aim for elimination of one variable by making the coefficients of either [tex]\( y \)[/tex] or [tex]\( x \)[/tex] the same in both equations. Here, we will eliminate [tex]\( y \)[/tex]. To do this, we need the coefficients of [tex]\( y \)[/tex] in both equations to be the same.
- Multiply Equation 1 by 4:
[tex]\[ 4(7x + 3y) = 4 \cdot 10 \implies 28x + 12y = 40 \quad \text{(Equation 3)} \][/tex]
- Multiply Equation 2 by 3:
[tex]\[ 3(4x + 4y) = 3 \cdot 8 \implies 12x + 12y = 24 \quad \text{(Equation 4)} \][/tex]
3. Subtract Equation 4 from Equation 3 to eliminate [tex]\( y \)[/tex]:
[tex]\[ (28x + 12y) - (12x + 12y) = 40 - 24 \][/tex]
Simplifying, we get:
[tex]\[ (28x - 12x) + (12y - 12y) = 16 \][/tex]
[tex]\[ 16x = 16 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ 16x = 16 \][/tex]
[tex]\[ x = \frac{16}{16} \][/tex]
[tex]\[ x = 1 \][/tex]
5. Substitute [tex]\( x = 1 \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex]. Let's use Equation 2:
[tex]\[ 4x + 4y = 8 \][/tex]
Substituting [tex]\( x = 1 \)[/tex]:
[tex]\[ 4(1) + 4y = 8 \][/tex]
[tex]\[ 4 + 4y = 8 \][/tex]
[tex]\[ 4y = 8 - 4 \][/tex]
[tex]\[ 4y = 4 \][/tex]
[tex]\[ y = \frac{4}{4} \][/tex]
[tex]\[ y = 1 \][/tex]
Thus, the solution set is [tex]\((x, y) = (1, 1)\)[/tex].
[tex]\[ \boxed{(1, 1)} \][/tex]
1. Write down the given system of equations:
[tex]\[ \begin{cases} 7x + 3y = 10 \quad \text{(Equation 1)} \\ 4x + 4y = 8 \quad \text{(Equation 2)} \end{cases} \][/tex]
2. Aim for elimination of one variable by making the coefficients of either [tex]\( y \)[/tex] or [tex]\( x \)[/tex] the same in both equations. Here, we will eliminate [tex]\( y \)[/tex]. To do this, we need the coefficients of [tex]\( y \)[/tex] in both equations to be the same.
- Multiply Equation 1 by 4:
[tex]\[ 4(7x + 3y) = 4 \cdot 10 \implies 28x + 12y = 40 \quad \text{(Equation 3)} \][/tex]
- Multiply Equation 2 by 3:
[tex]\[ 3(4x + 4y) = 3 \cdot 8 \implies 12x + 12y = 24 \quad \text{(Equation 4)} \][/tex]
3. Subtract Equation 4 from Equation 3 to eliminate [tex]\( y \)[/tex]:
[tex]\[ (28x + 12y) - (12x + 12y) = 40 - 24 \][/tex]
Simplifying, we get:
[tex]\[ (28x - 12x) + (12y - 12y) = 16 \][/tex]
[tex]\[ 16x = 16 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
[tex]\[ 16x = 16 \][/tex]
[tex]\[ x = \frac{16}{16} \][/tex]
[tex]\[ x = 1 \][/tex]
5. Substitute [tex]\( x = 1 \)[/tex] back into one of the original equations to solve for [tex]\( y \)[/tex]. Let's use Equation 2:
[tex]\[ 4x + 4y = 8 \][/tex]
Substituting [tex]\( x = 1 \)[/tex]:
[tex]\[ 4(1) + 4y = 8 \][/tex]
[tex]\[ 4 + 4y = 8 \][/tex]
[tex]\[ 4y = 8 - 4 \][/tex]
[tex]\[ 4y = 4 \][/tex]
[tex]\[ y = \frac{4}{4} \][/tex]
[tex]\[ y = 1 \][/tex]
Thus, the solution set is [tex]\((x, y) = (1, 1)\)[/tex].
[tex]\[ \boxed{(1, 1)} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.